Determinants of access to HIV testing and counselling services among female sex workers in sub-Saharan Africa: a systematic review - Soori Nnko; Evodius Kuringe; Daniel Nyato; Mary Drake; Caterina Casalini; Amani Shao; Albert Komba; Stefan Baral; Mwita Wambura; John Changalucha (BMC, 2019)
Abstract Background HIV testing and counselling (HTC) is an essential component for HIV prevention and a critical entry point into the HIV continuum of care and treatment. Despite the importance of HTC for HIV control, access to HTC services among female sex workers (FSWs) in sub-Saharan Africa (SSA) remains suboptimal and little is known about factors influencing FSWs' access to HTC. Guided by the client-centred conceptual framework, we conducted a systematic review to understand the facilitators and barriers influencing FSWs in SSA to access HTC services. Methods A systematic search was conducted in MEDLINE, POPLINE and Web of Science databases for literature published between January 2000 and July 2017. References of relevant articles were also searched. We included primary studies of any design, conducted in SSA and published in the English language. Studies conducted in multi-sites inclusive of SSA were included only if data from sites in SSA were separately analysed and reported. Similarly, studies that included other subpopulations were only eligible if a separate analysis was done for FSWs. This review excluded papers published as systematic reviews, editorial comments and mathematical modelling. The protocol for this review is registered in the Prospective Register of Systematic Reviews (PROSPERO), registration number CRD42017062203. Results This review shows that factors related to approachability, acceptability, availability, affordability and appropriateness of the services are crucial in influencing access to HTC services among FSWs in SSA. These factors were mediated by individual attributes such as HIV risk perceptions, awareness of the availability of HTC, and perceptions of the importance and quality of HTC services. The decision to utilise HTC was predominantly hampered by discriminatory social norms such as HIV stigma and criminalisation of sex work. Conclusions FSWs' access to HTC is facilitated by multiple factors, including individual awareness of the availability of HTC services, and perceived quality of HTC especially with regard to assured confidentiality. Concerns about HIV stigma and fear about discrimination due to community intolerance of sex work acted as major barriers for FSWs to seek HTC services from the facilities offering health services to the general population.